Effect of forage Legetan (Synedrella nodiflora) fresh and hay on the physical quality of forage pellets - Suwignyo, Bambang (2022)
This study aimed to determine the effect of raw materials Legetan in the form of fresh and hay on the physical quality of pellets. Legetan (Synedrella nodiflora) was used as main ingredient, in the form of fresh and hay. The research method used a Randomized Completely Block Design (RCBD). Then, if there was a significant difference, it will be analyzed further using Duncan multiple range test (DMRT). The treatments consisted of P1 = 10% rice bran + 90% fresh Legetan; P2 = 20% rice bran + 80% fresh Legetan; P3 = 10% rice bran + 90% hay Legetan; P4 = 20% rice bran + 80% hay Legetan. The variables measured were rendement, color, texture, and price. The results showed that the utilization of Legetan forage as raw material, both hay and fresh with the proportions of rice bran either 10:90 or 20:80, had no significant effect on the physical quality of Legetan forage pellets. However, the higher the portions of Legetan forage in the forage pellets, the more affordable the pellet price will be.